Diagnosis of ink disease of chestnut by molecular identification of associated phytophthora species - Gouveia, Maria Eugénia (2014)
For diagnostic proposes of ink disease, chestnut orchards with symptoms of decline or sudden death of trees were sampled by soil baiting techniques and selective agar media (P10VPH). Thirty-six Phytophthora isolates were obtained. One isolate per tree and three or two isolates from the soil of the same plant were considered for molecular identification. Genomic DNA was extracted from all the isolates and from the reference strain P. cinnamomi CECT 2965. The ribosomal regions ITS1, 5.8S and ITS2 were amplified with the universal primer pair ITS6 (Cooke and Duncan, 1997) and ITS4 (White et al., 1990) by PCR. The amplified fragment (900 pb) was digested with restriction enzymes MspI, AluI and TaqI. Two different patterns of fingerprinting were obtained with enzymes TaqI and AluI (type I and II) and three different patterns with MspI (type I, Ia, II). The fingerprinting of each isolate was compared with database of CABI by public web access. Type I and Ia (14 isolates) were assigned to P. cinnamomi and type II (4 isolates) was assigned to P. cambivora. Molecular methods provide a rapid means of Phytophthora species identification associated with ink disease of chestnut and will provide a useful tool for etiological and epidemiological studies of this important disease of chestnut.